The left and right sides of journalism in Malaysia / Nur Edzriena Narizal ... [et al.] - Narizal, Nur Edzriena; Azman, Nur Danish Qurnia; Saifuddin, Nabila Nuraisyah; Mohammad Nazmi, Mohammad Afiq; Mohamed Taufik, Mohamed Belqaiyum (2018)
This research are more likely to empirical and scientific research relate to opinion, feeling and thoughts by selected info1mants that related to our case study. This to identify the limitation of journalism. Besides that, this research is to identify how neutrality impacts the world of journalism. Moreover, this research is to identify differences between liberalism and conservatism and its effect towards Journalism perspective in Malaysia. For this research, we use qualitative method. We conducted interview session with seven informants through varieties medium included video conference, face off interview and via email as well. The first one is Pn. Noorzati Mohd Arish who is news producer at Media Prima TV News Network. Media Prima Berhad was selected because they have the most credibility staff and well-known company in Malaysia. The second one is En.Abdul Latiff Abu Bakar, a winner of the highest award in journalism field on 1986. Follow up by En. Syafiq Aznan and En. Azis Ngah who were happened to be sport journalist at Berita Harian. Next, En. Ibrahim Isa who is a journalist at Harian Metro and En. Amar Shah Mohsen that work as theSun reporter. Lastly, En. Adam Sulaiman Abdul Rahman, a team lead social media at Media Prima Radio Network who is also a former entertainment writer. Our finding show that media is playing an even bigger role in our society and what they publish is instantly being the common belief. So journalists bear the burden of ensuring that what they write is the truth so that the public is influenced by it. However, due to the limitations of the media in this country, some truths are withheld from the people and prove to be a challenge to write the news. Theory that can be related to the case studies is agenda setting theory. It pointed out that the media dominates over the creation of pictures in our head.